MENUJU PAUD MANDIRI: PELATIHAN SISTEMATIS MANAJEMEN KELAS BERORIENTASI KURIKULUM MERDEKA - Nasikhah, Ikha Durrotun; Suhasto, Firman Priyo; Rosfalia, Nihna Atho’a; Zulaiha, Mailinda Anis (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to improve the capacity of early childhood education (PAUD) teachers in independently managing classrooms through systematic classroom management training focused on the Merdeka Curriculum. This activity is driven by the low level of understanding and skills of teachers in implementing classroom management principles in accordance with the spirit of independent learning, which emphasizes enjoyable, child-centered, and contextual learning. The implementation method of this service adopts a participatory approach with a continuous training model consisting of three stages: needs assessment, in-depth training, and implementation mentoring. This activity was conducted over three months and involved 20 early childhood education teachers in the Gumukmas District as participants. The results of the activity show significant progress in teachers' understanding of classroom management concepts, their ability to create classroom management plans in accordance with the Merdeka Curriculum, and the implementation of appropriate and responsive teaching strategies to meet students' needs. In addition, the participants showed an increase in their independence in managing a safe and motivating learning environment. The recommendation from this activity is the importance of further training and periodic mentoring, as well as cooperation between educational institutions and local governments to support the sustainability of efficient classroom management practices in early childhood education (PAUD). The results of this research are expected to serve as a reference for educational institutions in designing similar training models in other regions.